At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
9514 1404 393
Answer:
f(4) -g(4) = 2
Step-by-step explanation:
Fill in the given values for x and do the arithmetic.
f(4) = 9·4 -2 = 34
g(4) = 2·4^2 = 32
Then ...
f(4) -g(4) = 34 -32
f(4) -g(4) = 2
ANSWER= 2
Explanation
Plug in the numbers in the parentheses for x EX: f(4)=9(4)-2= 34 and g(4)=2(4)^2 —-> g(4)=2(16)= 32 so 34-32= 2
Explanation
Plug in the numbers in the parentheses for x EX: f(4)=9(4)-2= 34 and g(4)=2(4)^2 —-> g(4)=2(16)= 32 so 34-32= 2
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.